2022
DOI: 10.1002/cche.10613
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of bran components with refined flour: Impact on protein solubility and their associations with whole wheat bread‐baking quality

Abstract: Background and Objectives: Bran components cause poor dough and end-product quality for whole wheat flour. However, there are few reports on the impacts of bran components on protein functionality in whole wheat bread-baking. Therefore, a reconstitution research was performed to evaluate bran components' effects on proteins in whole-wheat bread-baking. Findings: The bran components showed significant (p < .05) and complex impacts on the solubility of proteins in bread crumbs. Specifically, the fiber had synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Previous research that was performed using an experimental long‐flow mill in this laboratory showed a large variation for the physicochemical and bread‐making characteristics in hard red spring (HRS) wheat millstreams (Baasandorj et al, 2021). Among bran components, fiber was primarily responsible for deteriorative impacts on protein functionality with degradation of dough stability and bread‐making quality (Khalid et al, 2017; Simsek et al, 2023). Arabinoxylan, which is the main component of bran fiber, was particularly recognized as an effective differentiative index to evaluate the contamination level of bran components and bread‐making quality in flour millstreams (Baasandorj et al, 2021; Izydorczyk, 2021; Wang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research that was performed using an experimental long‐flow mill in this laboratory showed a large variation for the physicochemical and bread‐making characteristics in hard red spring (HRS) wheat millstreams (Baasandorj et al, 2021). Among bran components, fiber was primarily responsible for deteriorative impacts on protein functionality with degradation of dough stability and bread‐making quality (Khalid et al, 2017; Simsek et al, 2023). Arabinoxylan, which is the main component of bran fiber, was particularly recognized as an effective differentiative index to evaluate the contamination level of bran components and bread‐making quality in flour millstreams (Baasandorj et al, 2021; Izydorczyk, 2021; Wang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The grain also contains bran and germ which improves the nutritional density (11). The maize bran is rich in magnesium, phosphorus and potassium (12), although the bran and germ are normally excluded in refined flours (13,14). Maize is a source of protein, fibre and fat although the amount is greatly influenced by the variety of maize (15).…”
Section: Introductionmentioning
confidence: 99%